Revisiting Freedom’s Debtors - Scanlan, Padraic (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2019)
This essay reconsiders Freedom’s Debtors through the lens of the three Ferguson Prize panelists’ comments. It frames the arguments of the book in relationship to a growing body of scholarship on the history of Sierra Leone, and in relationship to older problems in the history of British imperial political economy. The essay reasserts two of the core contentions in Freedom’s Debtors: the close, and sometimes unacknowledged, proximity between British slavery and British antislavery, and the centrality of antislavery to British imperial expansion in the nineteenth century.